Rab27a controls HIV-1 assembly by regulating plasma membrane levels of phosphatidylinositol 4,5-bisphosphate - Pereyra Gerber, Federico Pehuén (2015)
During the late stages of the HIV-1 replication cycle, the viral polyprotein Pr55Gag is recruited to the plasma membrane (PM), where it binds phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) and directs HIV-1 assembly. We show that Rab27a controls the trafficking of late endosomes carrying phosphatidylinositol 4-kinase type 2 α (PI4KIIα) toward the PM of CD4+ T cells. Hence, Rab27a promotes high levels of PM phosphatidylinositol 4-phosphate and the localized production of PI(4,5)P2, therefore controlling Pr55Gag membrane association. Rab27a also controls PI(4,5)P2 levels at the virus-containing compartments of macrophages. By screening Rab27a effectors, we identified that Slp2a, Slp3, and Slac2b are required for the association of Pr55Gag with the PM and that Slp2a cooperates with Rab27a in the recruitment of PI4KIIα to the PM. We conclude that by directing the trafficking of PI4KIIα-positive endosomes toward the PM, Rab27a controls PI(4,5)P2 production and, consequently, HIV-1 replication.